Experimental research of neutron yield and spectrum from deuterium gas-puff z-pinch on the GIT-12 generator at current above 2 MA - Cherdizov R. K.; Fursov F. I.; Kokshenev V. A.; Kurmaev N. E.; Labetsky A. Yu.; Ratakhin N. A. Nikolay Aleksandrovich; Shishlov A. V. Aleksandr Viktorovich; Cikhardt J.; Cikhardtova B.; Klir D.; Kravarik J.; Kubes P.; et al. (High-current electronics, 2017)
Title screen